2019
DOI: 10.35591/wahana.v22i2.170
|View full text |Cite
|
Sign up to set email alerts
|

AKUNTABILITAS DAN TRANSPARANSI PADA LAPORAN KEUANGAN PARTAI (Studi Kasus pada Kantor DPD Partai Demokrat Provinsi Jawa Timur)

Abstract: Penelitian ini bertujuan untuk mengetahui dan memaknai akuntabilitas dan transparansi pada laporan keuangan DPD partai Demokrat Provinsi Jawa Timur yang terdiri dari laporan keuangan internal, laporan dana kampanye dan laporan bantuan politik serta implementasi AD dan ART partai Demokrat Provinsi Jawa Timur. Obyek yang digunakan dalam penelitian adalah kantor DPD partai Demokrat Provinsi Jawa Timur dengan metode penelitian kualitatif interpretif dengan etnometodologi sebagai pendekatan, terdapat empat informan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…At the same time, it also revealed state social assistance ( bansos ) and vote buying on the morning before the election as the last tactics to win (Rosana, 2024c). Another important report was Widodo's attempts to solidify his political support by offering minister seats in his current cabinet that will dissolve in October 2024 (Adyatama, 2024b). A comparable theme, “Enquête Right to Investigate Fraud in the 2024 Election” was chosen for the edition published March 10.…”
Section: Systematic Involvement Of Public and State Actorsmentioning
confidence: 99%
“…At the same time, it also revealed state social assistance ( bansos ) and vote buying on the morning before the election as the last tactics to win (Rosana, 2024c). Another important report was Widodo's attempts to solidify his political support by offering minister seats in his current cabinet that will dissolve in October 2024 (Adyatama, 2024b). A comparable theme, “Enquête Right to Investigate Fraud in the 2024 Election” was chosen for the edition published March 10.…”
Section: Systematic Involvement Of Public and State Actorsmentioning
confidence: 99%
“…Furthermore, research conducted by (Widayanti et al, 2023) on Accountability and Transparency in Party Financial Reports (Case Study at the DPD Office of the Democratic Party of East Java Province). The results showed that internal financial reports have fulfilled accountability to internal political parties but not transparency to the public.…”
Section: Introductionmentioning
confidence: 99%